2022
DOI: 10.34172/aim.2022.54
|View full text |Cite
|
Sign up to set email alerts
|

Major Depressive Disorder in Iran: Epidemiology, Health Care Provision, Utilization, and Challenges

Abstract: One in eight adults in Iran is estimated to have major depressive disorder (MDD) – a leading cause of disability in the country. Many remain undiagnosed, and some receive only partial treatment. An estimated 60% of those with MDD were reported to have received no treatment during the past year. In this paper, we have critically reviewed the current health-care structure in the country along with prevailing patterns of health-care service utilization. We have addressed the role of psychiatrists, general practit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…On average, 8% of the patients who are hospitalized due to other reasons are affected by MDD. In Iran, data from the national mental health survey (IranMHS) showed that 12.7% of the adult population had suffered from MDD in the past twelve months [ 4 ], and 41.2% of them had received any health services for their mental problem [ 42 ]. This means that if electronic health records are used, approximately 40% of adults with past twelve MDD will be found, and the remaining 60% will remain in the unexposed or healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…On average, 8% of the patients who are hospitalized due to other reasons are affected by MDD. In Iran, data from the national mental health survey (IranMHS) showed that 12.7% of the adult population had suffered from MDD in the past twelve months [ 4 ], and 41.2% of them had received any health services for their mental problem [ 42 ]. This means that if electronic health records are used, approximately 40% of adults with past twelve MDD will be found, and the remaining 60% will remain in the unexposed or healthy group.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, on average 8% of the patients who are hospitalized due to other reasons are affected by MDD. In Iran, data from the national mental health survey (IranMHS) showed that 12.7% of the adult population had suffered from MDD in the past twelve months [20], 41.2% of them had received any health services for their mental problem [37]. This means that if we use electronic health records, about 40% of adults with past twelve MDD will be found, and the rest 60% will retain in unexposed or healthy group.…”
Section: Strengths and Limitationsmentioning
confidence: 99%